Fruit and vegetable processing and consumption: Knowledge, attitude, and practices among rural women in East Africa - Jacob Sarfo; Elke Pawelzik; Gudrun B. Keding (Food Security, 2023)
High post-harvest losses of fruits and vegetables (FVs) limit their supply and availability for year-round consumption. Hence, processing innovations at their production areas could help address this constraint, which requires the need to assess people's perceptions in these areas. Therefore, this study gauged the knowledge, attitude, and practices towards FV processing and consumption and its relationship with actual FV consumption. Surveys were conducted with women in six study sites – three fruit and three vegetable production areas – in Kenya, Tanzania, and Uganda. Quantitative 24-h dietary and 7-day FV recalls were collected across two seasons. Open and closed-ended questions were constructed to assess the women's knowledge, attitude, and practices towards FV processing and consumption. The fruit and vegetable sites included 584 and 732 women, respectively. Average fruit consumption was 4-135~g/day in the plenty season and 4-106~g/day in the lean season. Vegetable consumption was 112-146~g/day and 84-180~g/day in the plenty and lean season, respectively. There were significant consumption differences across seasons. Most women expressed high knowledge of FV processing and consumption benefits and showed a positive attitude towards FV processing and consumption. Yet, in practice, a small number of women process FVs largely due to limited processing know-how and equipment. The relationship between knowledge and attitude and FV consumption was negative or none. The high knowledge and positive attitude expressed, yet the limited processing know-how and equipment should be a basis for interventions to increase FV processing into nutritious products for better nutrition and to ensure their availability year-round.
Keywords: 630; Africa; Knowledge; attitude and practices; Fruits and vegetables; Food processing; Women; Rural areas